On the Sicilian species of Pseudomeira Stierlin (Coleoptera: Curculionidae: Entiminae) - Bellò, Cesare; Baviera, Cosimo (Zootaxa, 2011)
Six new species of the weevil genus Pseudomeira are described from Sicily:  Pseudomeira erinacea sp. n., Pseudomeira ficuzzensis sp. n., Pseudomeira himerensis sp. n., Pseudomeira natalii sp. n., Pseudomeira petrensis sp. n., Pseudomeira trinacriae sp. n..  A neotype of Pseudomeira reitteri (Vitale, 1903) and lectotype of Pseudomeira obscura (Solari & Solari, 1907) are designated. Pseudomeira flavipennis sicula (Seidlitz, 1865), incorrectly indicated from Sicily is newly listed under synonymy of Pseudomeira flavipennis (Jacquelin du Val, 1852). Pseudomeira obscurella Bellò & Pierotti, 1994, is newly recorded for Sicily. Distribution and ecology are provided for each species as well as keys for identification, map and figures.